Composition Operator, Boundedness, Compactness, Hyperbolic Bloch-Type Space βμ∗, Hyperbolic-Type Space. (1st August 2020) - Tang, Shuan; Wu, Pengcheng
Abstract : In this paper, we obtain some characterizations of composition operators C φ, which are induced by an analytic self-map φ of the unit disk Δ, from hyperbolic Bloch type space β μ ∗ into hyperbolic type space Q K, p, q ∗ .